Combretastatin Derivatives as Microtubule Inhibitors of Colchicines Binding Site - Sahu, Adarsh (Anti-Infective Agents, 2022)
The colchicine binding site in microtubules is the most flourishing target for anticancer treatment. Microtubule inhibitor drugs, including paclitaxel and vinca alkaloids, have been considered to exert their activity primarily by increasing or decreasing the cellular microtubule mass. This review describes the microtubular assembly along with the combretastatin derivatives as microtubules inhibitors, the structures of compounds known to interact with colchicines binding sites, and their possible mechanism of action. Additionally, the utility of other heterocyclic rings and their combretastatin derivatives in treating cancer is also discussed. Colchicines binding site represents a stimulating new molecular target in the design of combretastatin drugs.
Keywords: aplha-tubulin